Exploring the involvement of the alternative complement pathway in non-infectious uveitis pathogenesis - Kulshrestha, Prerna; Goel, Pallavi; Murthy, Somasheila; Tyagi, Mudit; Basu, Soumvaya; Gogri, Pratik; Kaur, Inderjeet (Frontiers in Immunology, 2023)
Purpose Non-infectious uveitis is a complex disease characterized by intraocular inflammation of the uveal area and the leading cause of vision impairment and blindness in young people globally. However, what triggers inflammation and contributes to its recurrence remains unclear. The complement system has been linked to various immunological and inflammatory conditions. In the present study, we have systematically evaluated the role of the alternative complement pathway in the pathogenesis of non-infectious uveitis. Methodology Quantitative PCR was done in the peripheral leukocytes to study the expression of genes and regulatory miRNA in both anterior and posterior uveitis (n=28 in each category). Multiplex ELISA was performed to measure alternative pathway complement components, such as C3b, factor B, and CFH, and aqueous humor of infectious and non-infectious uveitis patients and non-inflammatory controls (n=10 each). Western blotting was done to validate the ELISA findings in a subset of patients and controls. Results Downregulation of C3 and CFH mRNA in the peripheral blood was shown by quantitative PCR in the group of anterior uveiits (AU), while the opposite result was found in the group of posterior uveitis (PU). ELISA levels of C3b and CFH proteins were significantly higher in aqueous humor of infectious and non-infectious uveitis (*p = 0.03 and **p = 0.0007 respectively) as compared to the control group. Western blotting further validated (VitH) the activation of the complement cascade in the aqueous (AH) and vitreous humor of patients with non-infectious uveitis, with an increased level of C3b (n=6) and CFH (n=4) in aqueous humor. C3b level was significantly increased while CFH was reduced relative to controls in the vitreous humor (VitH) of posterior uveitis patients compared to controls (n=27 in each category). A C3b to CFH ratio was computed to assess the regulation of complement activation and this index was several folds higher in both anterior and posterior uveitis (n=10 each). The expression of miRNA-hsa-miR-146a and miRNA-hsa-miR-155-5p that regulates CFH was downregulated and nicely correlated with the increased complement proteins in both anterior and posterior uveitis (n=10 each). Conclusion Our results demonstrate a clear role of CFH and the activation of the alternative complement pathway in the pathogenesis of non-infectious uveitis; however, its therapeutic potential warrants further investigations.